(2x^3-x^2-19x-10)/(2x+5)=x^2-3x-2 с методом разделение многочлена на многочлена
a=1,b=-3,c=-2
a+b+c=-4
проверка
(2х^3-x^2-19x-10)=(2x+5)(x^2-3x-2)
I.
1) 18у⁵-12ху²+9у³= 3у²·(6у³-4х+3у)
2) - 14аb³с²-21a²bc²-28a³b²c= -7abc·(2b²c+3ac+4a²b)
II.
1) a(3x-2y)+b(3x-2y) = (3x-2y)·(a+b)
2) (x+3)(2y-1)-(x+3)(3y+2)= (x+3)·(2y-1-3y-2)=(x+3)·(-y-3) = - (x+3)·(y+3)
III.
1) 3x-x²=0
x· (3-x) = 0
x₁ = 0;
3-x = 0 => x₂ = 3
ответ: {0; 3}
2) y²+5y=0
y·(у+5) = 0
у₁ = 0
у+5=0 => y₂ = -5
ответ: {0; -5}
IV.
27³+3⁷ = (3³)³ + 3⁷ = 3⁹ + 3⁷ = 3⁷· (3² + 1) = 3⁷· (9+1) = 3⁷ · 10
Понятие "кратно 10" означает "деление на 10 нацело"
(3⁷·10) : 10 = 3⁷ Доказано!
ax^2+bx+c=x^2-3x-2. Отсюда: a=1, b=-3, c=-2. Значит, a+b+c=1-3-2=-4